Classification and Control of Key Factors Affecting the Failure of Aviation Piston Turbocharger Systems Using Model-Based System Safety Analysis - Mengyao Bao; Shuiting Ding; Guo Li (International Journal of Aerospace Engineering)
Turbocharging is an effective way to address the problem of reduction in power and increase in fuel consumption of aviation piston engines during high-altitude flight. However, turbochargers have greatly increased the degree of complexity of power systems. The model-based system safety analysis methods for the safety analysis of turbocharging systems are introduced in this study to overcome the limitations of the traditional safety analysis methods regarding complex matching and coupled safety issues. On the basis of the established system models and the formed failure mode work boundaries and safety boundaries, the column profile coordinates F of correspondence analysis with the numerical deviation of the key factors are used to identify the key factors affecting failure, thereby proposing safety control strategies in a targeted manner. Then, the failure probability of the turbocharging system is assessed through the Monte Carlo method. System failure modes and probabilities before and after the execution of safety control strategies are compared to accurately determine the effectiveness of those strategies. The verification examples show that a safety control strategy that adjusts the diameter of the wastegate e2 can reduce system failure probability and enhance safety level.